2021
DOI: 10.1016/j.jvs.2021.01.065
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of post-endovascular aortic repair rupture during 15 years

Abstract: Objective: The devastating event of a ruptured abdominal aortic aneurysm (rAAA) in patients who have survived a previous AAA repair, either elective or urgent, is a feared and quite uncommon event. It has been suggested to partly explain the loss of the early survival benefit for endovascular aortic repair (EVAR) vs open surgical repair (OSR). The main objective of this study was to report the national incidence rate, risk factors and outcome of post-EVAR ruptures. Secondarily, the national incidence rate of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…9 Additionally, a recent study describing 86 patients with post-EVAR ruptures showed that a rAAA as the index surgery almost doubled the risk for post-EVAR rupture (hazard ratio 2.4). 2 In this study, 16 cases (out of all 86 post-EVAR ruptures; 18.6%) with rAAA as the cause were described; the mean time to post-EVAR rupture was 16 months compared to 47 months in patients with intact AAAs at index. Interestingly, 5 out of the 15 admitted patients were not treated and subsequently no safe conclusions regarding the outcome of this subgroup of patients can be extracted.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…9 Additionally, a recent study describing 86 patients with post-EVAR ruptures showed that a rAAA as the index surgery almost doubled the risk for post-EVAR rupture (hazard ratio 2.4). 2 In this study, 16 cases (out of all 86 post-EVAR ruptures; 18.6%) with rAAA as the cause were described; the mean time to post-EVAR rupture was 16 months compared to 47 months in patients with intact AAAs at index. Interestingly, 5 out of the 15 admitted patients were not treated and subsequently no safe conclusions regarding the outcome of this subgroup of patients can be extracted.…”
Section: Discussionmentioning
confidence: 79%
“…Aortic occlusion balloon is indicated in hemodynamically unstable patients. [2][3][4][5] Stent-graft extensions to proximal anchoring sites (cuffing, palmarization stents, embolization techniques) or distally (bridging stent-graft) can occlude the aneurysm. If the aneurysm is not anatomically feasible for secondary EVAR or the patient is hemodynamically unstable, open conversion may be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these four cases of rupture resulted in death, while the other two were successfully treated by emergent re-intervention (re-EVAR in one and OAR in one). The incidence rate of late rupture is reported to be 1.3–7% [ 7 , 22 25 ]. A Swedish national investigation performed by Andersson et al demonstrated that the independent risk factors for late rupture were ruptured AAA at initial EVAR and age.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of late aneurysm rupture in the present study was comparable to that in previous studies. This complication must not be neglected, and close long-term follow-up after EVAR is required [ 7 , 21 25 ].…”
Section: Discussionmentioning
confidence: 99%